The effects of a group study activities program on Islamic learning promotion among elderly Muslims in Yarang district, Pattani province, Thailand - Laeheem, Kasetchai; Tepsing, Punya; Promsaka Na Sakolnakorn, Thongphon; Azizskul, Hasbullah (Kasetsart Journal of Social Sciences, 2021)
The objective of this study was to explore effects of group study activities program on Islamic learning promotion among elderly Muslims in Yarang District, Pattani Province. Data were collected from a target group of 54 informants selected through purposive sampling from those with low scores on Islamic learning evaluation. The data were analyzed using one-way ANOVA and paired sample t-test. The study found that before participation in the practical experiment, the scores on Islamic learning promotion evaluation of all four groups of elderly Muslims were not different on the three aspects: having Islamic behavior, teaching and training their children and grandchildren, and being a good role model for their children and grandchildren. However, after the practical experiment, their scores on all the three aspects were significantly higher at the level .001. After the practical experiment, all four groups of elderly Muslims had similar results for their Islamic learning evaluation in all three aspects.